Ordini mendicanti e ospedali a Benevento (secoli XII-XIV) - Araldi, Giovanni (Quaderni di storia religiosa medievale, 2025)
The attitudes of the clergy and laity of Benevento towards the theme of involuntary poverty and human suffering changed profoundly after the arrival in the city of the Franciscans and Dominicans in the 1230s (the Augustinians were attested for the first time in 1284 and the Carmelites only at the beginning of the 15th century). The impact of their presence, strengthened in the second half of the century by the construction of their large convents in central areas of the town, was in fact decisive in spreading a spirituality aimed at action and active commitment to helping others, to which women in particular were sensitive, expressing a strong religious protagonism. This materialized both in the entry in the female branches of the first two mendicant orders and in the participation in "irregular" experiences, conducted alone or together with other devotees of both sexes, among which stand out those that arose around hospitals, of ancient foundation or born from the impulse of new ideals, which constitute one of the main threads of the research.